Pengaruh Motivasi Berwirausaha terhadap Minat Berwirausaha Mahasiswa Universitas Sahid Jakarta di Masa Pandemi Covid-19 - Lestari, Rima Ayunda; Kasman, Kasman; Hamdanur, Peris (Lembaga Publikasi Ilmiah Nusantara, 2023)
This study aims to describe the entrepreneurial motivation and entrepreneurial interest of Sahid University Jakarta students during the Covid-19 pandemic, and to determine the effect of entrepreneurial motivation on entrepreneurial interest during the Covid-19 pandemic. The data collection technique used was by distributing questionnaires and literature studies. The population for collecting this data is active students at Sahid University, Jakarta. The number of samples taken was 100 respondents using the purposive sampling method. The analytical method used was descriptive method and simple linear regression with SPSS ver.26. The results of the study showed that there was a significant influence between entrepreneurial motivation and interest in entrepreneurship. Furthermore, in order to increase the level of student entrepreneurship motivation towards student entrepreneurship interest, the University of Sahid Jakarta needs to help its students to develop their hard skills and soft skills. So that students can grow their interest in entrepreneurship, especially during the Covid-19 pandemic.